Wissenschaftsstädte — Wissenschaftsparks: Wissensbasierte Siedlungsstrukturen in deutschen Stadtregionen - Kühn, Manfred (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Basing on the indicator density of high research and development (R&D) and its spatial distribution in Germany, the article presents a typology of knowledge-based settlements. University-campi, technology parks, science parks, science cities and knowledge-based city landscapes are to be distinguished. The article questions its effects in regard to general trends of suburbanisation, desurbanisation and reurbanisation within city regions. Concluding, the author reflects to what extend it seems possible to stimulate innovative milieus by planning categories as proximity, mixed-uses and density.